Incorporating citizen science into IUCN Red List assessments - Rachael Gallagher; Erin Roger; Jasmin Packer; Cameron Slatyer; Jodi Rowley; Will Cornwell; Emilie Ens; Sarah Legge; Colin Simpfendorfer; Ruby Stephens; Thomas Mesaglio (Conservation Biology, 2025)
Many citizen scientists are highly motivated to help address the current extinction crisis. Their work is making valuable contributions to protecting species by raising awareness, identifying species occurrences, assessing population trends, and informing direct management actions, such as captive breeding. However, clear guidance is lacking about how to use existing citizen science data sets and how to design effective citizen science programs that directly inform extinction risk assessments and resulting conservation actions based on the International Union for Conservation of Nature (IUCN) Red List criteria. This may be because of a mismatch between what citizen science can deliver to address extinction risk and the reality of what is needed to inform threatened species listing based on IUCN criteria. To overcome this problem, we examined each IUCN Red List criterion (A–E) relative to the five major types of citizen science outputs relevant to IUCN assessments (occurrence data, presence–absence observations, structured surveys, physical samples, and narratives) to recommend which outputs are most suited to use when applying the IUCN extinction risk assessment process. We explored real‐world examples of citizen science projects on amphibians and fungi that have delivered valuable data and knowledge for IUCN assessments. We found that although occurrence data are routinely used in the assessment process, simply adding more observations of occurrence from citizen science information may not be as valuable as inclusion of more nuanced data types, such as presence–absence data or information on threats from structured surveys. We then explored the characteristics of citizen science projects that have already delivered valuable data to support assessments. These projects were led by recognized experts who champion and validate citizen science data, thereby giving greater confidence in its accuracy. We urge increased recognition of the value of citizen science data within the assessment process.

Molecular Variation and Evolutionarily Significant Units in the Endangered Gila Topminnow - Karen M. Parker; Ruby J. Sheffer; Philip W. Hedrick (Conservation Biology, 1999)
Determining evolutionarily significant units in endangered species is one of the most significant challenges facing conservation biology. Often genetic information has been used as the primary basis of recommendations for evolutionarily significant units, but these data should be evaluated carefully and used in conjunction with other information. The endangered Gila topminnow ( Poeciliopsis. o. occidentalis ) has been the subject of extensive conservation biology research and genetic investigation. We extended these data to highly variable genetic markers, examined variation in microsatellite loci, and compared it with previous measures of genetic diversity for the Gila topminnow from the four watersheds in Arizona in which they are still naturally extant. Fish from Monkey Spring were the most highly differentiated from the other populations. Overall, the amounts and patterns of genetic variation were consistent with known historical and physical differences among sites. The four watersheds are highly physically isolated from one another and differ in a number of important factors in their physical habitat, biota, and the life‐history of the topminnows. Based on these geographic patterns and the genetic results, we recommend that the four watersheds all be managed and conserved separately.

Fitness in the Endangered Gila Topminnow - Ruby J. Sheffer; Philip W. Hedrick; W. L. Minckley; Anthony L. Velasco (Conservation Biology, 1997)
The Gila topminnow (Poeciliopsis o. occidentalis) is a small, live‐bearing, endangered fish extant in a maximum of nine locales in four separate watersheds in the United States. To determine if these populations differed in their fitness, we obtained samples from the four watersheds and examined them for four fitness correlates: survival, growth rate, fecundity, and bilateral asymmetry. Earlier research found that one population, Sharp Spring, had higher allozyme heterozygosity than the other three and had higher survival, growth rate, and fecundity and lower bilateral asymmetry than a sample from one of the other populations with no polymorphic allozyme loci, Monkey Spring. We also verified that Sharp Spring fish were polymorphic for the same allozyme loci whereas the Monkey Spring population was not. We did not, however, find positive associations of allozyme heterozygosity with the four fitness correlates for the four samples. Because the earlier study had much lower survival, it is likely that the differences resulted from differential response of the two populations to a stressful laboratory environment. Whether this unknown stress occurs in natural environments or its effect is predictive of other stresses remains unresolved. As a result, we concur with suggestions in the draft recovery plan that topminnows from nearby sources be used for reintroductions and that the Sharp Spring stock not be used outside the upper Santa Cruz River drainage.